Proton Pump Inhibitors – Their Pharmacological Impact on the Clinical Management of Acid-Related Disorders - Klotz, Ulrich (Arzneimittelforschung, 2009)
Acid secretion or intragastric pH play a very important role in the pathophysiology of acid-related disorders such as peptic ulcer (PU), gastrooesophageal reflux disease (GERD) or nonsteroidal anti-inflammatory drug (NSAID)-induced gastrointestinal lesions. Proton pump inhibitors (PPIs) represent the most potent/effective antisecretory drugs for these indications. For the selection among the various agents (omeprazole/esomeprazole (CAS 73590-58-6/119141-88-7), pantoprazole (CAS 102625-70-7), lansoprazole (CAS103577-45-3), rabeprazole (CAS 117976-83-3)) some features of their pharmacokinetic (PK) and pharmacodynamic (PD) properties should be considered as the clinical outcome depends on systemic drug exposure (PK) and elevation of intragastric pH about certain threshold levels (PD).The present review updates PK, PD and clinical data to provide some guidance between the PPIs which differ somewhat in their metabolic pattern and drug interaction potential. Based on 24-h intragastric pH assessments the relative potencies of the PPIs compared to omeprazole were in healthy volunteers (in GERD patients): 0.42 (0.59), 1.0 (0.8), 1.0 (1.0), 1.25 (1.25) and 2.0 (1.4) for pantoprazole, lansoprazole, omeprazole, esomeprazole and rabeprazole, respectively. In general, the clinical benefits of PPI are well documented but some patients can be regarded as non-responders and thus represent a challenge for future clinical research.
Keywords: Esomeprazole; Helicobacter pylori infection; Lansoprazole; Omeprazole; Pantoprazole; Peptic ulcer; Proton pump inhibitors, pharmacodynamics, pharmacokinetics; Rabeprazole; Reflux disease